Health providers’ perceptions on language barriers in Catalonia’s public healthcare system - Rubio-Carbonero, Gema; Gil-Bardají, Anna (Revista de Llengua i Dret, 2025)
In this article, we present the results of an exploratory quantitative study on the situation of communication between healthcare staff in the Catalan public system and users with limited competence in the official languages of Catalonia. The study objective is to offer a comprehensive and empirically grounded overview of the current state of intercultural communication in the Catalan public health system, with and without the involvement of third-party mediation, as perceived by healthcare providers. Data were collected through a structured questionnaire administered to professionals engaged in direct patient care across public health centres in Catalonia, yielding a sample of 1 390 respondents. The findings underscore the high frequency and significant impact of language barriers in clinical encounters and highlight notable deficiencies in the resources currently available to address these challenges. , Aquest article presenta els resultats d’un estudi quantitatiu exploratori sobre la situació de la comunicació entre el personal sanitari del sistema públic català i els usuaris que tenen un coneixement limitat de les llengües oficials de Catalunya. L’objectiu de l’estudi és oferir una visió global i amb una base empírica de l’estat actual de la comunicació intercultural en el sistema públic de salut català –tant amb la mediació de tercers com sense– a partir de la percepció que en tenen els professionals sanitaris. Les dades es van recollir mitjançant un qüestionari estructurat administrat a professionals que treballen en l’atenció directa als pacients en centres públics de salut de Catalunya, que va permetre obtenir una mostra de 1.390 participants. Els resultats posen de manifest l’alta freqüència i el fort impacte de les barreres lingüístiques en les interaccions clíniques, així com mancances notables en els recursos disponibles actualment per afrontar aquests reptes. , Este artículo presenta los resultados de un estudio cuantitativo exploratorio sobre la situación de la comunicación entre el personal sanitario del sistema público catalán y los usuarios con un conocimiento limitado de las lenguas oficiales de Cataluña. El objetivo del estudio es ofrecer una visión global y con base empírica del estado actual de la comunicación intercultural en el sistema público de salud catalán –tanto con la mediación de terceros como sin ella– a partir de la percepción de los profesionales sanitarios. Los datos se recogieron mediante un cuestionario estructurado administrado a profesionales que trabajan en la atención directa al paciente en centros públicos de salud de Cataluña, con el que se obtuvo una muestra de 1.390 participantes. Los resultados ponen de manifiesto la elevada frecuencia y el fuerte impacto de las barreras lingüísticas en las interacciones clínicas, así como carencias notables en los recursos disponibles actualmente para afrontar tales desafíos.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.